Catheter directed interventions for inferior vena cava thrombosis - Golowa, Yosef (Cardiovasc Diagn Ther, 2016)
Inferior vena cava (IVC) thrombosis, although similar in many aspects to deep venous thrombosis (DVT), has distinct clinical implications, treatments and roles for endovascular management. Etiologies of IVC thrombosis vary from congenital malformations of the IVC to acquired, where indwelling IVC filters have been implicated as a leading cause. With an increasing incidence of IVC thrombosis throughout the United States, clinicians need to be educated on the clinical signs and diagnostic tools available to aid in the diagnosis as well as available treatment options. Untreated IVC thrombus can result in serious morbidity and mortality, both in the acute phase with symptoms related to venous outflow occlusion and embolism, and in the long-term, sequelae of post-thrombotic syndrome (PTS) related to chronic venous occlusion. This manuscript will discuss the clinical presentation of IVC thrombosis, diagnostic and treatment options, as well as the role of endovascular management.